Further Insights in the Most Common SCN5A Mutation Causing Overlapping Phenotype of Long QT Syndrome, Brugada Syndrome, and Conduction Defect - Veltmann, Christian (J Am Heart Assoc, 2016)
BACKGROUND: Phenotypic overlap of type 3 long QT syndrome (LQT3), Brugada syndrome (BrS), cardiac conduction disease (CCD), and sinus node dysfunction (SND) is observed with SCN5A mutations. SCN5A‐E1784K is the most common mutation associated with BrS and LQTS3. The present study examines the genotype–phenotype relationship in a large family carrying SCN5A‐E1784K and SCN5A‐H558R polymorphism. METHODS AND RESULTS: Clinical work‐up, follow‐up, and genetic analysis were performed in 35 family members. Seventeen were SCN5A‐E1784K positive. They also displayed QTc prolongation, and either BrS, CCD, or both. One carrier exhibited SND. The presence of SCN5A‐H558R did not significantly alter the phenotype of SCN5A‐E1784K carriers. Fourteen SCN5A‐E1784K patients underwent implantable cardioverter‐defibrillator (ICD) implantation; 4 developed VF and received appropriate ICD shocks after 8±3 months of follow‐up. One patient without ICD also developed VF after 6.7 years. These 5 cases carried both SCN5A‐E1784K and SCN5A‐H558R. Functional characterization was achieved by expressing SCN5A variants in TSA201 cells. Peak (I(Na,P)) or late (I(Na,L)) sodium currents were recorded using whole‐cell patch‐clamp techniques. Co‐expression of SCN5A‐E1784K and SCN5A‐WT reduced I(Na,P) to 70.03% of WT, shifted steady‐state inactivation by −11.03 mV, and increased I(Na,L) from 0.14% to 1.86% of I(Na,P). Similar changes were observed when SCN5A‐E1784K was co‐expressed with SCN5A‐H558R. CONCLUSIONS: We demonstrate a strong genotype‐phenotype correlation with complete penetrance for BrS, LQTS, or CCD in the largest family harboring SCN5A‐E1784K mutation described so far. Phenotype of LQTS is present during all decades of life, whereas CCD develops with increasing age. Phenotypic overlap may explain the high event rate in carriers.